Using stirring power curves to investigate the air-entrainment and mechanical properties of cement mortar at low air pressure. (16th May 2023) - Zeng, Xiao-Hui; Lan, Xu-Li; Zhu, Hua-Sheng; Ran, Yu-Zhou; Umar, Hussaini Abdullahi; Teng, Guo-Cui; Wu, Jun-Qing; Zhou, Yun-Xian; Peng, Jie-Bo; Long, Guang-Cheng
Graphical abstract: Highlights: This study explored the effect of low air pressure, a new factor, on properties of air-entrained cementitious materials. Stirring power curve was adopted to study the air-entrainment of cement-based materials at low air pressure. The optimum mixing speed for air-entrainment at low air pressure is recommended. A new method is proposed to regulate air content of cement-based materials in plateau. Abstract: With more infrastructures being built in plateau areas, low atmospheric pressure has been suggested as a new factor affecting the air-entrainment and mechanical properties of concrete. However, the influence and mechanism of low air pressure on cement-based materials are still ambiguous. This study investigates the air-entrainment of cementitious materials at low air pressure for the first time using stirring power curves and homogenization work. Results show that the homogenization work at low pressure is 22.5 %-96.4 % higher than at standard pressure, which is attributed to the lower air content of samples and poor stability of air bubbles at low pressure; for the first time, the optimum stirring speed for air-entrainment at low pressure is recommended; the air-voids parameters of low-pressure samples are unusual; and the compressive strength increased by 4.3 %, 6.7 %, and 9.4 % at the age of 7 days, 14 days, and 28 days, respectively, when air pressure drops from 101 kPa to 50 kPa. The mechanisms of low air pressure on the properties of cementitious materials are expounded. This study proposes a new method to regulate air-entrainment of cement-based materials in plateaus, in addition to providing a comprehensive explanation of the effects and principles of low air pressure on behaviours of cementitious materials.